Speleothem stable isotope reference records resampled to evenly spaced time-series - István Gábor Hatvani; Zoltán Kern; Attila Demény (PANGAEA, 2017)
Uneven spacing is a common feature of sedimentary paleoclimate records, in many cases causing difficulties in the application of classical statistical and time series methods. Although special statistical tools do exist to assess unevenly spaced data directly, the transformation of such data to a temporarily equidistant time series applicable to commonly used statistical tools remains, however, an unachieved goal. The present paper, therefore, introduces an approach to obtain evenly spaced time series (using cubic spline fitting) from unevenly spaced speleothem records with the application of a spectral guidance to avoid spectral bias caused by interpolation and retain the original spectral characteristics of the data. The methodology was applied to stable carbon and oxygen isotope records derived from two stalagmites of the Baradla Cave (NE Hungary) dating back to the late 18th century; it was also applied to additional well-dated and high-resolution stable isotope records from the Han-sur-Lesse Cave (Belgium). To show the benefit of these equally spaced records to climate studies, their coherence with primary and complex climate indices is explored using wavelet transform coherence and discussed.
Supplement to: Hatvani, István Gábor; Kern, Zoltán; Leél-Őssy, Szabolcs; Demény, Attila (2018): Speleothem stable isotope records for east-central Europe: resampling sedimentary proxy records to obtain evenly spaced time series with spectral guidance. Earth System Science Data, 10(1), 139-149, https://doi.org/10.5194/essd-10-139-2018